Foreword - Abd Rahim, Alhan Farhanah (Electrical Engineering Studies, 2026)
Welcome to this edition of E Waves. As we reflect on the journey throughout 2025, I am truly proud of how the Faculty, particularly the Electrical Engineering Studies community, has continued to grow in strength, resilience, and excellence. This year would not have been possible without the dedication and collective effort of our lecturers, assistant engineers, and students. Each contribution, whether in teaching, research, laboratory support, innovation activities, student development, or community engagement, has played an important role in shaping the achievements and milestones highlighted in this bulletin. Your commitment and teamwork are the driving force behind the continued excellence of PKE. I would like to express my sincere appreciation to everyone who has contributed their time, expertise, and passion throughout the year. May this bulletin serve not only as a record of our accomplishments, but also as a source of motivation as we move forward together into the coming year with renewed purpose and ambition. Thank you for being part of this journey and for continuously striving to make PKE a place of growth, innovation, and inspiration.